Analysis of Morphology of Erythrocytes and Their Resistance Depending on pH and Ionic Strength Under Hypothermal Storage - Repin, N. V.; Kiroshka, V. V.; Golovko, O. I. (Problems of Cryobiology and Cryomedicine, 2009)
It has been shown that the observed relationship between transformation of cell shape and their osmotic resistance as well as damage degree during hypothermal storage (HS) is stipulated by ionic strength and equilibration medium pH. The degree of cell damage in non-electrolyte media during HS is statistically lower and their osmotic resistance is higher if compared with electrolyte ones. The most resistant to the factors of medium is echinocyte shape of erythrocytes.